Experimental validation of a dual uplink multifrequency dispersive noise calibration scheme for Deep Space tracking. Issue 2 (22nd March 2013) - Mariotti, G.; Tortora, P.
<x xml:space="preserve">Abstract</x> We discuss the implementation and effectiveness of a dispersive noise multifrequency calibration scheme for Deep Space tracking. We show that the combination of two phase‐coherent links at X band and Ka‐band, with two separate uplink carriers, can provide an effective plasma and ionospheric noise removal, in the order of 75% of the plasma noise affecting the Ka‐band link. This algorithm, which we refer to as "Dual Uplink, Dual Downlink", shows a modest loss in the radio link stability, if compared to the complete, state‐of‐the‐art calibration achieved by a more complex radio system, which supplements the two separate uplinks and downlinks at X band and Ka‐band with an additional "cross‐link" (X‐up/Ka‐down). The calibration accuracy of these two algorithms is thoroughly compared to define their advantages and shortcomings. Finally, Cassini's multifrequency tracking data acquired in 2002 during a General Relativity solar conjunction experiment aimed at the estimation of the parametrized post Newtonian parameter γ were reanalyzed to assess the capability of the Dual Uplink, Dual Downlink calibration algorithm to support accurate radio science experiments.